The predictive value of serum SCUBE-1 level for left ventricular thrombus in patients with post myocardial infarction heart failure - Ozgul, Ufuk; Ozturk, Bayram; Kerkutluoglu, Murat; Yucel, Oguzhan; Bolayir, Hasan Ata; Baylan, Filiz Alkan; Gunes, Hakan (Walter de Gruyter Gmbh, 2022)
Objectives Left ventricular thrombus is regarded as one of the main myocardial infarction complications. Knowing the left ventricular thrombus symptoms prevents serious complications that may occur. This study aims to reveal any association between SCUBE-1 and left ventricular thrombus, thought to be involved in platelet aggregation and adhesion. Methods The study included 80 patients diagnosed with heart failure following acute myocardial infarction, applying for the cardiology outpatient clinic for third-month follow-up. The patients were included in two groups to see if the left ventricular thrombus was present. Thus, 22 patients were found to have left ventricular thrombus. The two groups were compared based on clinical laboratory and echocardiographic parameters. Results It was found that the patients with left ventricular thrombus had significantly higher Serum SCUBE-1 levels (p<0.001). The optimal cutoff point of SCUBE-1 levels for predicting the LVT was >35.1 ms, with the specificity of 86% and sensitivity of 68.4% (AUC=0.815; 95% CI, 0.699-0.931; p<0.0001). SCUBE -1 level (OR=1.090, 95% CI: 1.034-1.150, p<0.001) in the multiple logistic regression model continue to significantly predict LVT after adjusting for the confounding variables, as statistically significant in the univariate analysis of the variables which correlated with the SCUBE-1 levels. Conclusions SCUBE-1 level was determined to independently predict the left ventricular thrombus after a previous anterior myocardial infarction.
Miyokard enfarktüsü sonrası kalp yetmezliği olan hastalarda sol ventrikül trombüsü için serum SCUBE-1 seviyesinin prediktif değeri
Keywords: acute myocardial infarction; left ventricular thrombus; LVT; SCUBE-1